Peranan Pembina Asrama Dalam Membimbing Pelaksanaan Ibadah Salat Fardu Siswi di Asrama Putri Mts N 3 Lima Puluh Kota - Fauziyyah Fitriani; Rita Febrianta (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Based on the problems that researchers found in the field, female students were still found neglecting prayers, chatting and making noise when arranging the rows, as well as a lack of supervision and control from the dormitory supervisors. The aim to be achieved in the results of this research is to determine the role of dormitory supervisors in guiding the implementation of fardu prayers, as well as to determine the supporting and inhibiting factors for dormitory supervisors in guiding the implementation of fardu prayers. The research method that the author used for this research was descriptive qualitative field research. The key informant in this research was the dormitory supervisor, while the supporting informants were twenty female dormitory students who were interviewed. In collecting the required data, the author carried out observations, interviews with informants and documentation. After the data is obtained, it is then processed using descriptive data analysis and data triangulation by comparing data obtained from observations, interviews and documentation. Based on the research results, the role of the dormitory supervisor in guiding the implementation of fardu prayers for female students in the women's dormitory at MTs N 3 Limapuluh Kota is that the dormitory supervisor provides explanations, teaches related movements, reading prayers, dhikr and prayers. Dormitory supervisors also provide facilities in the form of a series of alarms to remind you of prayer times. Provide warnings and other sanctions for those who violate the rules. Collaborating with parents, dormitory supervisors coordinate using WhatsApp Group (WAG) to send documentation photos of children's activities in the dormitory, as well as a worship control book. It's just that here because of the lack of time for dormitory supervisors to control and supervise female students in carrying out fardu prayers.